An automated system for interrogating the evolution of microbial endosymbiosis. Issue 4 (13th October 2022) - Huang, Can; Guo, Fengguang; Wang, Han; Olivares, Jasmine; Dalton, III, James; Belyanina, Olga; Wattam, Alice R.; Cucinell, Clark A.; Dickerman, Allan W.; Qin, Qing-Ming; Han, Arum; de Figueiredo, Paul
Abstract : Using an automated microfluidic SEER platform, we rapidly evolved laboratory naïve E. coli strain DH5α to possess enhanced capability to survive within host cells, and identified the critical role of gene CpxR in such microbial endosymbiosis. Abstract : Inter-kingdom endosymbiotic interactions between bacteria and eukaryotic cells are critical to human health and disease. However, the molecular mechanisms that drive the emergence of endosymbiosis remain obscure. Here, we describe the development of a microfluidic system, named SEER (S̲ystem for the E̲volution of E̲ndosymbiotic R̲elationships), that automates the evolutionary selection of bacteria with enhanced intracellular survival and persistence within host cells, hallmarks of endosymbiosis. Using this system, we show that a laboratory strain of Escherichia coli that initially possessed limited abilities to survive within host cells, when subjected to SEER selection, rapidly evolved to display a 55-fold enhancement in intracellular survival. Notably, molecular dissection of the evolved strains revealed that a single-point mutation in a flexible loop of CpxR, a gene regulator that controls bacterial stress responses, substantially contributed to this intracellular survival. Taken together, these results establish SEER as the first microfluidic system for investigating the evolution of endosymbiosis, show the importance of CpxR in endosymbiosis, and set the stage for evolving bespoke inter-kingdom endosymbiotic systems with novel or emergent properties.